SOSIALISASI PENGOLAHAN BAWANG PUTIH TUNGGAL DALAM BENTUK BLACK GARLIC SEBAGAI POTENSI DESA BANTAN TENGAH KECAMATAN BANTAN KABUPATEN BENGKALIS - Rezi Abdurrahman; Yuafrizal Yuafrizal; Putri Aurelia; Putri Martika; Amniatizzakia Amniatizzakia; Annisa Alifhia Zuhri; Mirza Irdina; Defri Indrawan; Suhadha Armanda Prayoga; M Ridho Agustiawan; Nurul Hafizah (Universitas Pahlawan Tuanku Tambusai, 2022)
Today, herbal plants are very widely used as alternative healing and are very much researched. Garlic is one of the ingredients that is often used as an ingredient in cooking. Apparently, in addition to being used as food ingredients, it can be used as herbal medicine. Garlic has been widely used as a traditional medicine for many years. In 3000 BC, Chinese scientists have tested and analyzed the benefits of garlic. The ancient Greek scholar Aristotle also tested garlic in 335 BC for medicinal use. This community service aims to provide socialization in Bantan Tengah Village, Bantan District, Bengkalis Regency in order to utilize kitchen spices that are often used as cooking ingredients so that the community can later provide economic value, so that it can help the community's economy both individually and in the household and analyze potential Black Garlic in Central Banten Village. This method of implementing community service is carried out through socialization and education activities through counseling, mentoring and training with various main and supporting activity programs. The basic properties in Black Garlic are able to be antioxidants and can ward off free radicals. The well-known compounds are polyphenols, S-alllyl and flavonoids. Some of the benefits of black garlic help lower cholesterol, triglycerides, uric acid and high blood pressure, normalize blood sugar, prevent cancer and other diseases. Keywords: Black Garlic, Community Service, Village Potential, Socialization